Análise do comprimento médio de telômeros de leucócitos em indivíduos com apneia obstrutiva do sono, insônia e ambos os distúrbios associados: um estudo de base populacional - Tempaku, Priscila Farias [UNIFESP] (2017)
Analysis of mean leukocyte telomere length in individuals obstructive sleep apnea, insomnia and both disorders associated: a population-based study. 2017. 129p. MSc Dissertation - Department of Psychobiology. Universidade Federal de Sao Paulo, Sao Paulo, Brazil. Throughout life, there is significant alterations in quantity and quality of sleep, characterized by reduction in its duration and higher prevalence of sleep disorders such as insomnia and obstructive sleep apnea (OSA). Although the sleep pattern of the elderly is well-known, the relationship between sleep and the aging-related mechanisms is not clarified. Thus, the present study aimed to determine the relationship between the mean leukocyte telomere length (LTL) with sleep parameters and the presence of OSA, insomnia, insomnia associated with sleep duration and both associated sleep disorders in an adult population. For this, we used DNA collected and extracted from peripheral blood of 928 individuals from the EPISONO. All individuals were subjected to one full-night polysomnography. OSA was determined according to apnea-hypopnea index (AHI). Iindividuals with an AHI≥15 were classified as OSA, while those with AHI<15 were considered as controls. Insomnia was evaluated following the 4th edition of Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) and when associated with sleep duration, it was additionally evaluated through weighted self-reported total sleep time. For the measurement of LTL, we used the quantitative real-time polymerase chain reaction method in a multiplex format. The results showed negative correlations between LTL and the following variables: apnea-hypopnea index, desaturation index and wake after sleep onset. LTL was also positively correlated with sleep efficiency, total sleep time and basal, lowest and mean oxygen saturation. LTL was significantly shorter in OSA (1.27 ± 0.1) compared to controls (1.38 ± 0.1) (p=0.047). However we did not find a significant association between OSA severity and LTL (p=0.437). Insomnia was not statistically associated with LTL (p=0.823). However, among the long sleepers, insomnia individuals presented shorter LTL (1.28 ± 0.1) compared to controls (1.45 ± 0.1) (p=0.021). Moreover, we did not observe a significant association of both sleep disorders (insomnia+OSA) (1.32 ± 0.1) on LTL (p=0.466). Our data indicates that, differently from insomnia, OSA by itself may have a significant role in the shortening of telomeres. Added to this, when associated with sleep duration, the present study suggests that insomnia may be associated with cellular aging. Thus, we conclude that there is a relationship between the pathophysiological mechanisms of sleep and the molecular pathways of cellular aging related to telomere length maintenance.